Sudden cardiac death in young people and athletes - Domenico Corrado; Alessandro Zorzi (Italian Journal of Medicine, 2018)
The sudden death of a young subject or athlete is a rare but tragic event. The most common mechanism of cardiac arrest leading to sudden death is abrupt ventricular fibrillation as a consequence of an underlying cardiovascular disease. The culprit diseases are often clinically silent and unlikely to be suspected or diagnosed on the basis of spontaneous symptoms. The longrunning Italian experience with medical evaluation of young individuals before their participation in sports has provided compelling evidence that screening the young populations for at-risk cardiac diseases offers the potential to identify asymptomatic athletes who have potentially lethal cardiovascular abnormalities and may protect them from the risk of sudden death. In this review we will discuss cardiovascular causes of sudden death in young people and athletes with particular emphasis on pathological findings and pathophysiology of sudden cardiac arrest. Occurrence of prodromal symptoms, possible early diagnosis at preparticipation screening and early defibrillation in the sports arenas will also be addressed.